Different types of disease‐causing noncoding variants revealed by genomic and gene expression analyses in families with X‐linked intellectual disability. Issue 7 (3rd May 2021) - Field, Michael J.; Kumar, Raman; Hackett, Anna; Kayumi, Sayaka; Shoubridge, Cheryl A.; Ewans, Lisa J.; Ivancevic, Atma M.; Dudding‐Byth, Tracy; Carroll, Renée; Kroes, Thessa; Gardner, Alison E.; Sullivan, Patricia; et al.
Abstract: The pioneering discovery research of X‐linked intellectual disability (XLID) genes has benefitted thousands of individuals worldwide; however, approximately 30% of XLID families still remain unresolved. We postulated that noncoding variants that affect gene regulation or splicing may account for the lack of a genetic diagnosis in some cases. Detecting pathogenic, gene‐regulatory variants with the same sensitivity and specificity as structural and coding variants is a major challenge for Mendelian disorders. Here, we describe three pedigrees with suggestive XLID where distinctive phenotypes associated with known genes guided the identification of three different noncoding variants. We used comprehensive structural, single‐nucleotide, and repeat expansion analyses of genome sequencing. RNA‐Seq from patient‐derived cell lines, reverse‐transcription polymerase chain reactions, Western blots, and reporter gene assays were used to confirm the functional effect of three fundamentally different classes of pathogenic noncoding variants: a retrotransposon insertion, a novel intronic splice donor, and a canonical splice variant of an untranslated exon. In one family, we excluded a rare coding variant in ARX, a known XLID gene, in favor of a regulatory noncoding variant in OFD1 that correlated with the clinical phenotype. Our results underscore the value of genomic research on unresolved XLID families to aid novel, pathogenic noncoding variant discovery. Abstract : Multiomics finds three different non‐coding variants that cause intellectual disability.